Who knows? : a study of religious consciousness - Smullyan, Raymond M. (Indiana University Press, 2003)
Is there really a God, and if so, what is God actually like? Is there an afterlife, and if so, is there such a thing as eternal punishment for unrepentant sinners, as many orthodox Christians and Muslims believe? And is it really true that our unconscious minds are connected to a higher spiritual reality, and if so, could this higher spiritual reality be the very same thing that religionists call "God"? In his latest book, Raymond M. Smullyan invites the reader to explore some beautiful and some horrible.